The induction of laboratory-based amoebic gill disease revisited - Morrison, RN; Crosbie, PBB; Barbara Nowak (2004)
Previous work in our laboratory defined a method of inducing laboratory-based amoebic gill disease (AGD) in Atlantic salmon, Salmo salar L. Gills of AGD-affected fish were scraped and the debris placed into fish-holding systems, eliciting AGD in naïve Atlantic salmon. While this method is consistently successful in inducing AGD, variability in the kinetics and severity of infections has been observed. It is believed that the infections are influenced by inherently variable viability of postharvest amoeba trophozoites. Here, a new method of experimental induction of AGD is presented that redefines the infection model including the minimum infective dose. Amoebae were partially purified from the gills of AGD-affected Atlantic salmon. Trophozoites were characterized by light microscopy and immunocytochemistry and designated Neoparamoeba sp., possibly Neoparamoeba pemaquidensis. Cells were placed into experimental infection systems ranging in concentration from 0 to 500 cells L-1. AGD was detected by gross and histological examination in fish held in all systems inoculated with amoebae. The number of gross and histological AGD lesions per gill was proportional to the inoculating concentration of amoebae indicating that the severity of disease is a function of amoeba density in the water column. The implications of these observations are discussed in the context of the existing AGD literature base as well as Atlantic salmon farming in south-eastern Tasmania.